Toward Understanding Preferences for Sharing and Privacy - Olson, Judith; Grudin, Jonathan; Horvitz, Eric (2004)
E-commerce has spawned a growing concern and discussion about privacy. Similar concerns about privacy are emerging with ubiquitous computing applications that sense and report one’s location and activity. But sharing is as important as privacy; work and social interaction are more efficient when people share some information with some recipients. Unfortunately, commonly available tools for specifying who can see what have been too complex and tedious for most computer users. We report on studies of preferences about privacy and sharing aimed at identifying fundamental concerns with privacy and at understanding how people might abstract the details of sharing into higher-level classes of recipients and information that people tend to treat in a similar manner. To characterize such classes, we collected information about sharing preferences, recruiting 30 people to specify what information they are willing to share with whom. Although people vary in their overall level of comfort in sharing, we discovered key classes of recipients and information. Such abstractions highlight the promise of developing simpler, more expressive controls for sharing and privacy.